1983
DOI: 10.1287/mnsc.29.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and Adjusting for the Intervalling-Effect Bias in Beta

Abstract: The concept of beta as the measure of systematic risk has been widely accepted in the academic and financial community. Increasingly, betas are being used to estimate the cost of capital for corporations. Despite this, however, biases are generally present in ordinary least squares (OLS) estimates of beta. In particular, empirical estimates of beta are affected by friction in the trading process which delays the adjustment of a security's price to informational change and hence leads to an "intervalling-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(61 citation statements)
references
References 19 publications
3
55
0
3
Order By: Relevance
“…For example, Hawawini and Michel (1979) found a similar pattern of results on the Belgium stock exchange by using weekly interval returns data between 1963 and 1976. The result also follows Cohen et al (1983) hypothesis that there is a strong relationship between beta estimates and the length of the interval over which returns are measured. They established that beta bias mostly shows up in the short length interval (daily) of returns, and the bias disappears when the difference of the interval is lengthened (monthly).…”
Section: Beta Biassupporting
confidence: 76%
See 2 more Smart Citations
“…For example, Hawawini and Michel (1979) found a similar pattern of results on the Belgium stock exchange by using weekly interval returns data between 1963 and 1976. The result also follows Cohen et al (1983) hypothesis that there is a strong relationship between beta estimates and the length of the interval over which returns are measured. They established that beta bias mostly shows up in the short length interval (daily) of returns, and the bias disappears when the difference of the interval is lengthened (monthly).…”
Section: Beta Biassupporting
confidence: 76%
“…They proposed a variant version of Scholes and Williams model which yields betas which are consistent and unbiased. We use only three months lag and lead because beta bias has been documented as not prevalent in monthly returns data (see Cohen, Hawawini, Maier, Schwartz and Whitcomb (1983) …”
Section: Various Models For Estimating Betamentioning
confidence: 99%
See 1 more Smart Citation
“…Vasicek (1973) suggests a Bayesian correction for the bias. Cohen, Hawawini, Maier, Schwartz, and Whitcomb (1983) present an analytical model to adjust estimated beta by estimating the cross-sectional intervalthinness relationship. There is no agreement in the literature on which adjustment method is superior over the rest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is no agreement in the literature on which adjustment method is superior over the rest. Diacogiannis and Makri (2008) tested the efficiency of the Scholes and Williams (1977) and Cohen et al (1983) methods using Greek data. They found that neither method provides any incremental benefit over standard OLS estimation.…”
Section: Literature Reviewmentioning
confidence: 99%